(untitled) (Research, Society and Development, 2021)
The malignant neoplasm that is defined as cancer is a pathology with characteristics of uncontrolled cell enlargement that triggers an accumulation of malignant cells. Palliative care requires intervention in the care of patients in early, advanced or terminal stages, stimulating a process of easing or controlling the signs and symptoms. In this context, the role of the physiotherapist is to act in a complementary way to palliative treatment, with the aim of improving the individual’s recovery, restoring the functions of different parts of the body. The objective of this work is to discuss the importance of physical therapy intervention in oncology, with a focus on palliative care. Refers to a narrative literature review. For this article, manual searches were made on the Google Scholar platform and selected articles related to the theme. From the data presented, the role of physical therapy intervention is related to rehabilitation in all stages of the disease, in which pain is the most relevant occurrence causing great discomfort to the patient. Physiotherapy is an important area in the treatment of terminally ill patients, rehabilitating the motor condition and, therefore, inserting this individual in the resumption of functional independence. Finally, studies prove that physiotherapy has an important role in palliative care, however, definitions of care for palliative patients are necessary to be propagated among physiotherapists and research is necessary for a good professional improvement.